Capsinoids activate brown adipose tissue (BAT) with increased energy expenditure associated with subthreshold 18-fluorine fluorodeoxyglucose uptake in BAT-positive humans confirmed by positron emission tomography scan - Sun, Lijuan (2020)
Background: Capsinoids are reported to increase energy expenditure (EE) via brown adipose tissue (BAT) stimulation. However, imaging of BAT activation by capsinoids remains limited. Because BAT activation is a potential therapeutic strategy for obesity and related metabolic disorders, we sought to prove that capsinoid-induced BAT activation can be visualized by 18-fluorine fluorodeoxyglucose (18F-FDG) positron emission tomography (PET). Objective: We compared capsinoids and cold exposure on BAT activation and whole-body EE. Design: Twenty healthy participants (8 men, 12 women) with a mean age of 26 y (range: 21–35 y) and a body mass index (kg/m2) of 21.7 (range: 18.5–26.0) underwent 18F-FDG PET and whole-body calorimetry after ingestion of 12 mg capsinoids or ≤2 h of cold exposure (∼14.5°C) in a crossover design. Mean standardized uptake values (SUVs) of the region of interest and BAT volumes were calculated. Blood metabolites were measured before and 2 h after each treatment. Results: All of the participants showed negligible 18F-FDG uptake post-capsinoid ingestion. Upon cold exposure, 12 participants showed avid 18F-FDG uptake into supraclavicular and lateral neck adipose tissues (BAT-positive group), whereas the remaining 8 participants (BAT-negative group) showed undetectable uptake. Capsinoids and cold exposure increased EE, although cold induced a 2-fold increase in whole-body EE and higher fat oxidation, insulin sensitivity, and HDL cholesterol compared with capsinoids. Conclusions: Capsinoids only increased EE in BAT-positive participants, which suggests that BAT mediates EE evoked by capsinoids. This implies that capsinoids stimulate BAT to a lesser degree than cold exposure as evidenced by 18F-FDG uptake below the presently accepted SUV thresholds defining BAT activation. This trial was registered at www.clinicaltrials.gov as NCT02964442.